Characteristics of the nutritive status of canned meats in emergency "survival" rations - Popov, I G; Lozinskiĭ, P A; Latsekevich, A A; Romanova, I A (Kosmicheskaia biologiia i aviakosmicheskaia meditsina, 1983)
Variations in the nutrient status of test subjects who for 5 days were given a survival diet made of 400 g canned meat were investigated. The energy expenditures of the test subjects were 3000-3200 kcal/day. The study was performed under moderate climate conditions. Anthropometric and biochemical parameters, as well as nitrogen, amino acid, carbohydrate and mineral metabolism were investigated. It has been demonstrated that the survival diet of the above composition can be used by the flight personnel in a contingency situation under moderate climate conditions, provided that water supply is about 1 1/day. The study has shown sporadic hypoglycemia, intensive ketonemia, heavy salt losses, and early protein deficiency. This should be taken into consideration when arranging rescue operations, rehabilitation nutrition and pilot training. It is understood that adequate preflight nutrition may be of great importance.